Laboratory-scale biogas production from vegetable juice waste using an IC reactor - Boualy Vongvisith; Chengyue Liang; Changmei Wang; Fang Yin; Kai Wu; Bin Yang; Jing Liu; Hong Yang; Wudi Zhang (Academia Green Energy)
This investigation aimed to assess the performance of an internal circulation (IC) reactor in converting vegetable juice waste (VJW) into biogas and evaluating its methane content. The experiment involved collecting different types of leafy vegetable waste from a market in Chenggong County, Yunnan Province. The experimental procedure was divided into five phases based on organic loading rates (OLRs) of 1.4, 2.2, 4.4, 8.4, and 17.6 g COD/L.d, with hydraulic retention times (HRTs) of 6, 4, 2, 1, and 0.5 days, respectively. The experimental results showed that the biogas production rate was 2.6 L/d, and 66% methane content was achieved when the OLR was 1.4 g COD/L.d and the HRT was six days. The average daily biogas production and methane content were 3.72 L and 66%, respectively, with volumetric biogas and methane production rates of 1.4 and 0.93 L/L.d. The biogas production yield was higher in phase I, with a higher methane content. The variation in the methane content of the biogas generated remained constant between 66% and 69%. The efficiency of the IC reactor was reflected in the effluent chemical oxygen demand (COD) concentration reduction and the percentage of COD removal efficiency. The highest COD removal, 94%, occurred in phase I, with an OLR of 1.4 gCOD/L.d and an HRT of 6 days, compared to other phases. However, during the operation of the IC reactor, even with a decrease in the HRT, the system did not overload. The IC reactor system was found to be efficient in biogas production from VJW and wastewater treatment waste both currently and in the future.